Employee Job Satisfaction Rises with Motivation Compensation and Workplace Conditions: Kepuasan Kerja Karyawan Meningkat Melalui Motivasi Kompensasi dan Lingkungan Kerja - Ni Kadek Putri Indira Febrianti; Gunawan Wibisono; Komang Sudarsana (Universitas Muhammadiyah Sidoarjo, 2026)
General Background: Employee job satisfaction is an important factor in maintaining productivity, loyalty, and organizational stability. Specific Background: This study examined work motivation, compensation, and work environment in an incense production company with specific workplace conditions, including production aromas, piece-rate work, and different compensation arrangements for new employees. Knowledge Gap: Previous studies have shown inconsistent findings regarding the relationship between these three factors and employee job satisfaction. Aims: This study aimed to determine the partial and simultaneous roles of work motivation, compensation, and work environment in employee job satisfaction. Results: Data from 33 purposively selected employees were analyzed using multiple linear regression, t-tests, and F-tests with IBM SPSS Statistics 22. The findings showed that work motivation, compensation, and work environment had positive and significant roles both partially and simultaneously in employee job satisfaction. Novelty: This study provides evidence from a local production context with distinctive workplace challenges. Implications: Companies should strengthen motivation, improve compensation fairness, and create safer, cleaner, and more comfortable working conditions. Highlights • Individual predictors showed positive and significant statistical results.• Combined testing confirmed a meaningful contribution to staff contentment.• The production setting presented distinct challenges, including incense aroma and piece-rate systems. Keywords Work Motivation; Compensation; Work Environment; Job Satisfaction; Human Resource Management